The Effect of Heart Rate on Jump-Shot Accuracy of Adolescent Basketball Players - Padulo, Johnny; Nikolaidis, Pantelis T.; Cular, Drazen; Dello Iacono, Antonio; Vando, Stefano; Galasso, Maria; Lo Storto, Dario; Ardigò, Luca P. (Frontiers in Physiology, 2018)
Basketball is a team sport, where fundamental skills – fundamentals – are key determinants for success. Jump-shot (JS) is a basketball fundamental used frequently during game. It is interesting to spread light on the relationship between effort intensity and JS ability. Study aim was to investigate different heart rates (HRs) effect on JS accuracy (JS%) in 22 male youth (15.7±0.9 yrs) players. Experimental sessions consisted of 10 JSs from five spots 5-m from basket at three different HRs: rest (0HR) and after warm-up (50% [50HR] and 80% maximal HR [80HR]). Analysis of variance showed differences in JS% over sessions (42.27±14.78% at 0HR, 38.18±10.53% at 50HR, and 30.00±16.62% at 80HR; P=0.018). Least significant difference test did not show any significant difference between 50HR and 0HR JS% (P=0.343), while 80HR elicited significantly lower values with respect to both 0HR (P=0.006) and 50HR (P=0.049). Study provided practical indications on maintaining high JS%: preliminary warm-up (even if injury-protecting) does not improve JS%, because between 50HR and 0HR difference was not significant; and 80HR significantly decreases JS%. Therefore, to maximize JS scoring players have to rest as much as possible during game-play pauses, and coaches should manage timeouts and substitutions accordingly, especially during final minutes of close games.